Evaluating the impact of AED training on nurses’ emergency response capabilities in China: a cross-sectional survey - Qingxiu Long; Zhenyu Luo (BMC Nursing)
Abstract Background Automated external defibrillators (AEDs) are critical in emergency cardiac care. However, significant gaps in nurses’ knowledge and confidence in using AEDs limit their effectiveness. This study explores the current status of AED training and its impact on nurses’ emergency response capabilities across municipal-level and county-level hospitals in China. Methods A cross-sectional survey was conducted from May 20 to August 1, 2024, via telephone and electronic questionnaires in the emergency, intensive care unit (ICU), and general wards of 12 municipal and county-affiliated hospitals. A total of 451 questionnaires were distributed, with 440 valid responses (response rate: 97.6%). Data were analyzed using chi-square tests and multivariate logistic regression in SPSS 24.0 (P < 0.05 considered significant). Key factors influencing AED knowledge and confidence included additional training, hands-on drills, and defibrillation experience. Results Only 17.5% of nurses demonstrated sufficient AED knowledge, and 15.9% reported confidence in defibrillation. In municipal-level hospitals, nurses outperformed county hospitals in training access and proficiency. Additional training (OR = 24.50, p < 0.0001) and practical drills (OR = 12.36, p < 0.0001) were strongly associated with improved knowledge and confidence. Conclusions The study highlights the need for enhanced AED training, emphasizing practical drills and scenario-based simulations, particularly in resource-limited county hospitals. Targeted strategies could significantly improve nurses’ emergency response capabilities, contributing to better cardiac arrest outcomes.